The Administration of Garlic Extract on Eimeria stiedai Oocysts and the Hematological Profile of the Coccidia Infected Rabbits - D. Indrasanti; M. Indradji; S. Hastuti; E. Aprilliyani; Fatikha Fatikha; K. A. Rosyadi (Media Peternakan, 2017)
This research aimed to examine the potential of garlic as the coccidiosis control in rabbits either in vitro or in vivo. During in vitro, observed variables were rabbits oocysts that were sporulated, unsporulated, and abnormal in incubation for 3 days with the addition of garlic extract. The treatments were doses of garlic extract administration (0%, 1%, 2%, 4%, and 8%) and sulfaquinoxalline as a standard anticoccidiosis. Meanwhile during in vivo, the variables observed were the hematological profile of the experimental rabbits naturally infected with coccidia. The doses of garlic extract was administered orally to the experimental rabbits infected with coccidia were 0 mg, 10 mg, 20 mg, 40 mg, and 80 mg/rabbit.  As a standard coccidiosis drugs, the combination of sulfadiazine and trimethoprim was used.  The treatments were given for 6 days. The variables observed were the hematological profile of the coccidiosis rabbits, including the erythrocytes, hemoglobin, hematocrits, MCV, MCH, MCHC, and thrombocytes. The research employed a completely randomized design, with 5 repetitions. The data were further analyzed using the honestly significant difference test. The results showed that garlic extract administration significantly decreased (P<0.01) both the number of the sporulated and unsporulated oocysts (P<0.05), yet did not significantly influence the abnormal oocysts, but there was no significant difference within the entire hematological variables except in thrombocytes (P<0.05). Garlic extract administration decreased the excretion number of oocysts in the feces either in vitro or in vivo and influenced some hematological variables which provided a new propect for controlling coccidiosis naturally in rabbits.